2020
DOI: 10.3892/mmr.2020.11044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CD44 on differentiation of human amniotic mesenchymal stem cells into chondrocytes via Smad and ERK signaling pathways

Abstract: cd44 antigen (cd44) is a transmembrane protein found in cell adhesion molecules and is involved in the regulation of various physiological processes in cells. it was hypothesized that cd44 directly affected the chondrogenic differentiation of human amniotic mesenchymal stem cells (haMScs). in the present study, the expression of chondrocyte-associated factors was detected in the absence and presence of the antibody blocker anti-cd44 antibody during the chondrogenic differentiation of haMScs. Following inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…For example, trypsin dissociation significantly reduces CD44 expression, as well as other MSC surface markers, on human MSCs compared to other dissociation agents such as TrypLE (Tsuji et al, 2017 ). Further, CD44 expression may also affect the chondrogenic differentiation of human MSCs via the Smad 2/3 and ERK ½ signaling pathway (Xu et al, 2020 ). In UC blood-derived MSCs, Kwon et al ( 2019 ) demonstrated that CD44 has an immunoregulatory role as evidenced by the induction of macrophage polarization via CD44 expression by the proteoglycan, decorin.…”
Section: Challenges For Clinical Translation Of Mesenchymal Stromal Cmentioning
confidence: 99%
“…For example, trypsin dissociation significantly reduces CD44 expression, as well as other MSC surface markers, on human MSCs compared to other dissociation agents such as TrypLE (Tsuji et al, 2017 ). Further, CD44 expression may also affect the chondrogenic differentiation of human MSCs via the Smad 2/3 and ERK ½ signaling pathway (Xu et al, 2020 ). In UC blood-derived MSCs, Kwon et al ( 2019 ) demonstrated that CD44 has an immunoregulatory role as evidenced by the induction of macrophage polarization via CD44 expression by the proteoglycan, decorin.…”
Section: Challenges For Clinical Translation Of Mesenchymal Stromal Cmentioning
confidence: 99%
“…CD44 has important functions in cell–cell and cell-matrix interactions, including proliferation, hematopoiesis and lymphocyte activation, homing and extravasation [ 8 ]. CD44 is essential for maintaining cartilage homeostasis, influences the production of collagen II and aggrecan and influences the chondrodifferentiation of amniotic MSCs [ 9 ]. CD44 has been implicated in cancer, arthritis, interstitial lung disease, vascular disease, wound-healing and infections by pathogens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyaluronic acid, abundant in cartilage, connective tissues, and synovial fluid in our body, has excellent rheological and biochemical properties, and is an attractive material for bioink [ 81 , 82 ]. In particular, hyaluronic acid has been used for cartilage tissue regeneration, since it has the potential to induce chondrogenic differentiation due to the CD44 interaction with laden cells [ 83 , 84 ]. The use of hyaluronic acid as a bioink requires chemical modifications and/or mixing with other polymer materials, resulting in solidification of the fabricated 3D structure.…”
Section: Technologies For Bioinksmentioning
confidence: 99%